Advances in Diagnostic Approaches for Viral Etiologies of Diarrhea: From the Lab to the Field - Malik, Yashpal Singh; Verma, Atul Kumar; Kumar, Naveen; Touil, Nadia; Karthik, Kumaragurubaran; Tiwari, Ruchi; Bora, Durlav Prasad; Dhama, Kuldeep; Ghosh, Souvik; Hemida, Maged Gomaa; Abdel-Moneim, Ahmed S.; Bányai, Krisztián; et al. (Frontiers in Microbiology, 2019)
The applications of correct diagnostic approaches play a decisive role in timely containment of infectious diseases spread and mitigation of public health risks. Nevertheless, there is a need to update the diagnostics regularly to capture the new, emergent, and highly divergent viruses. Acute gastroenteritis of viral origin has been identified as a significant cause of mortality across the globe, with the more serious consequences seen at the extremes of age groups (young and elderly) and immune-compromised individuals. Therefore, significant advancements and efforts have been put in the development of enteric virus diagnostics to meet the WHO ASSURED criteria as a benchmark over the years. The Enzyme-Linked Immunosorbent (ELISA) and Polymerase Chain Reaction (PCR) are the basic assays that provided the platform for development of several efficient diagnostics such as real-time RT-PCR, loop-mediated isothermal amplification (LAMP), polymerase spiral reaction (PSR), biosensors, microarrays and next generation sequencing. Herein, we describe and discuss the applications of these advanced technologies in context to enteric virus detection by delineating their features, advantages and limitations.